THE RELEVANCE OF THE USE OF INNOVATIVE METHODS IN THE TEACHING OF MICROBIOLOGY - Koziraximova Nargiza Kodirjonovna; Khakimova Muslimakhon Akramkhanovna (Western European Studies, 2023)
This article explores the significance of incorporating innovative teaching methods in microbiology education. It delves into the current state of microbiology education, analyzes existing literature on traditional and modern teaching approaches, presents a variety of innovative methods, and discusses their potential impact on student learning outcomes. The article concludes with suggestions for implementing these methods and emphasizes the need for continual adaptation in microbiology education
Keywords: Microbiology education; active learning